The trap - Howard, Catherine Ryan (Blackstone Publishing, 2023)
"One year ago, Lucy's sister, Nicki, left to meet friends at a pub in Dublin and never came home. The third Irish woman to vanish inexplicably in as many years, the agony of not knowing what happened that night has turned Lucy's life into a waking nightmare. So, she's going to take matters into her own hands. Angela works as a civilian paper-pusher in the Missing Persons Unit, but wants nothing more than to be a fully-fledged member of An Garda Síochána, the Irish police force. With the official investigation into the missing women stalled, she begins pulling on a thread that could break the case wide open -- and destroy her chances of ever joining the force. A nameless man drives through the night, his latest victim in the back seat. He's going to tell her everything, from the beginning. And soon, she'll realize: what you don't know can hurt you ..."--